PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK SISTEM PEREDARAN DARAH MANUSIA BERBASIS INKUIRI TERMBIMBING MELALUI APLIKASI SIGIL UNTUK PEMBELAJARAN BIOLOGI SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The success of the learning process during the pandemic is influenced by several factors, one of which is the availability of teaching materials that are relevant to the applicable curriculum and integrated with technology such as electronic student worksheet. Making electronic student worksheet can be assisted using sigil software which has more complete features than similar software. This study aims to develop a quality guided inquiry-based electronic student worksheet for the human circulatory system using the sigil application. This research was conducted at the PMIPA FKIP Campus, Riau University, SMA N 1 Pekanbaru and MAN 1 Pekanbaru in July 2021-January 2022. This R&D research uses the ADDIE model which consists of analysis, design, and development stages. Quality data collection instruments in the form of validation sheets and response questionnaires. The results showed that the quality of the electronic student worksheet of the human circulatory system based on guided inquiry that was developed was very good with a quality value of 3.83, with details, namely the validation value of 3.89 with the very valid category and the limited trial value of 3.77 with the very good category. This study shows that the electronic student worksheet of the human circulatory system based on guided inquiry that was developed is of very good quality so that it can be used in the biology learning process in the classroom.Key Word: Electronic Student Worksheet, guided inquiry, sigil, human circulatory system